2021
DOI: 10.1111/mmi.14677
|View full text |Cite
|
Sign up to set email alerts
|

The pathway of recombining short homologous ends in Escherichia coli revealed by the genetic study

Abstract: The recombination of short homologous ends in Escherichia coli has been known for 30 years, and it is often used for both site‐directed mutagenesis and in vivo cloning. For cloning, a plasmid and target DNA fragments were converted into linear DNA fragments with short homologous ends, which are joined via recombination inside E. coli after transformation. Here this mechanism of joining homologous ends in E. coli was determined by a linearized plasmid with short homologous ends. Two 3ʹ‐5ʹ exonucleases ExoIII an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…S7 B ) by microhomology-mediated illegitimate recombination. Microhomologies of only very few nucleotides are known to cause deletions in nearly all biological systems, including bacteria ( 33 , 34 ), the eukaryotic nucleus ( 35 ), and also in chloroplasts ( 36 38 ). A possible mechanistic explanation for the observed instability in the hpRNA constructs but not the dsRNA constructs could be that the hpRNA cassette constantly undergoes flip-flop recombination between the sense and the antisense sequence of the transgene, and therefore, may be prone to recombination errors that result from the recombination machinery occasionally acting on microhomologies.…”
Section: Discussionmentioning
confidence: 99%
“…S7 B ) by microhomology-mediated illegitimate recombination. Microhomologies of only very few nucleotides are known to cause deletions in nearly all biological systems, including bacteria ( 33 , 34 ), the eukaryotic nucleus ( 35 ), and also in chloroplasts ( 36 38 ). A possible mechanistic explanation for the observed instability in the hpRNA constructs but not the dsRNA constructs could be that the hpRNA cassette constantly undergoes flip-flop recombination between the sense and the antisense sequence of the transgene, and therefore, may be prone to recombination errors that result from the recombination machinery occasionally acting on microhomologies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, using this enzyme is sufficient for the DNA assembly reaction not only for multiple DNA fragments but also for enabling the assembly of short fragments. While XthA has been studied in earlier studies in in vivo DNA assembly 13 , 15 , 16 , in this study, we have gone further in developing an in vitro DNA assembly method that uses only XthA to achieve the efficient assembly of multiple fragments, including short fragments. With SENAX, the homology ends are digested by XthA and annealed in vitro, while the resulting intermediates are being repaired (gap filling and covalently bonding) presumably inside the E.coli cells after transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The unique properties of the XthA enzyme also enabled its application in the catalysis of nucleoprotein complexes and even for the sequencing analysis of short DNA fragments 14 . Conley et al previously proposed that XthA in E. coli in vivo could help in the circularization of linear plasmids without homologies 15 , while very recently, Yang et al reported that the in vivo cloning activity of E. coli requires both XthA and ExoX 16 . In the same study, Yang et al also presented a minimal experiment using XthA for the circulation of a linear plasmid with a 24 bp homology arm.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of host strains is heavily relying on their availability. During our investigation on the complete pathway of the recombination of short-homologous ends in E. coli ( Yang et al, 2021 ), we noticed E. coli BW25113 may be efficient in cloning and DNA assembly. The significantly higher TE and cloning efficiency of E. coli BW25113 over commonly used E. coli strains are beyond our expectations ( Figures 1 , 5 ).…”
Section: Discussionmentioning
confidence: 99%